Laser-induced forward transfer based laser bioprinting in biomedical applications - Chang, Jinlong; Sun, Xuming (Frontiers in Bioengineering and Biotechnology, 2023)
Bioprinting is an emerging field that utilizes 3D printing technology to fabricate intricate biological structures, including tissues and organs. Among the various promising bioprinting techniques, laserinduced forward transfer (LIFT) stands out by employing a laser to precisely transfer cells or bioinks onto a substrate, enabling the creation of complex 3D architectures with characteristics of high printing precision, enhanced cell viability, and excellent technical adaptability. This technology has found extensive applications in the production of biomolecular microarrays and biological structures, demonstrating significant potential in tissue engineering. This review briefly introduces the experimental setup, bioink ejection mechanisms, and parameters relevant to LIFT bioprinting. Furthermore, it presents a detailed summary of both conventional and cutting-edge applications of LIFT in fabricating biomolecule microarrays and various tissues, such as skin, blood vessels and bone. Additionally, the review addresses the existing challenges in this field and provides corresponding suggestions. By contributing to the ongoing development of this field, this review aims to inspire further research on the utilization of LIFT-based bioprinting in biomedical applications.